Estudio poblacional del sula nebouxii en la reserva marina Isla Santa Clara, cantón Santa Rosa, provincia de El Oro - Jumbo Quezada, Ruth Carolina (2018)
The objective of this research work was to determine the current population status and distribution of the Sula nebouxii in the Santa Clara Island Marine Reserve. The Marine Reserves play a fundamental role in the conservation of marine biodiversity. Santa Clara Island is home to some of the most numerous colonies of the species Sula nebouxii throughout continental Ecuador, being the natural habitat chosen by the species sites near the coasts where they nest on flat surface with little vegetation. The research work is of great importance due to the fact that no research has been carried out on the species Sula nebouxii in the Santa Clara Marine Reserve, one of the problems being the lack of up-to-date information that allows the creation of research initiatives by students. , teachers and the community in general. According to the reports of the Provincial Directorate of the Environment El Oro, the population of the Sula nebouxii in the years 2015 and 2016 present a varied tendency registering high and low peaks in the number of individuals. Within the research phase to know the current population the following methods were used; the method of quadrants to establish the area of the censuses to apply, the count in fixed point to register the individuals and the sites in which the population is found, the observation and interviews to establish risk factors that have incidence in the species. It was determined that the population of chicks, juveniles and nests has been reduced compared to previous demographic data, this decrease reflects a problem in the reproductive and breeding success of the species.With regard to distribution, the species has a central distribution pattern, locating the largest population in quadrant "F", placing the rest of the population in lower concentration towards the periphery.